Gene expression profiling of SPIN1 in gastric cancer: insights into tumorigenesis and potential therapeutic targets - Bei-Bei Lv; Lei Cai; Yao Xiao; Rui-Han Wang; Xiao-Yan Lin (Frontiers in Genetics)
BackgroundGastric cancer (GC) is a prevalent malignant tumor globally, posing a significant threat to human health. The histone code reader Spindlin1 (SPIN1) has been implicated in tumorigenesis and tumor progression, however, the exact molecular mechanisms underlying these processes remain incompletely understood. The biological function and regulatory mechanisms of SPIN1 in GC remain ambiguous. This study aims to investigate the regulatory mechanisms of SPIN1 in the pathogenesis and progression of GC, as well as to identify genes closely associated with SPIN1 and potential biomarkers.MethodsGene expression profiles from 375 patients diagnosed with gastric cancer (GC) and 32 control subjects were obtained from the TCGA-STAD database. Our study examined the relationships between SPIN1 expression and various factors including tumor progression, clinical stage, survival status, immune microenvironment and drug sensitivity within the cohort of 375 GC patients and 32 controls. Furthermore, we investigated the interplay between m6A and 5 mC regulators in influencing the expression of SPIN1 in GC, and identified genes with significant correlations with SPIN1 through Spearman correlation analysis.ResultsA significantly elevated expression of SPIN1 was found in 375 GC patients compared to 32 control subjects. SPIN1 expression was positively correlated with EMT score and angiogenesis score. Cell proliferation-related gene sets (myogenesis, mitotic spindle and G2M checkpoint) were all significantly associated with the high SPIN1 GC group. Eosinophils was associated with high expression of SPIN1. A total of 21 checkpoints were associated with SPIN1 expression. Low SPIN1 expression group could benefit from Axitinib, Cytarabine, Pazopanib and Sunitinib. Most m6A regulators and a subset of m5C regulators were positively associated with SPIN1. Finally, we screened the 10 genes with the strongest correlation with SPIN1, among which CDH11 and SLC8A1 were associated with the prognosis of GC.ConclusionIn conclusion, our study has provided valuable insights into the pivotal role of SPIN1 in GC development, elucidating its potential molecular mechanisms and establishing it as a promising therapeutic target.